Republic of Kazakhstan : Staff Report for the 2001 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2002)
This 2001 Article IV Consultation for Kazakhstan highlights that real GDP growth in 2001 is expected to be about 13 percent, driven by the strong growth in the petroleum sector and associated spillover effects. Inflation has declined further to 6.4 percent in December (year-over-year). Gross international reserves of the National Bank of Kazakhstan have risen to USD 2.5 billion, which provides for about three months of import coverage. The general government surplus is projected to be about 3.3 percent of GDP in 2001, on account of higher oil revenue, but also reflecting economic buoyancy.